Development of an initiatives package to increase children's vegetable intake in long day care centres using the Multiphase Optimisation Strategy (MOST) randomised factorial experiment - Lucinda K Bell; Samantha Morgillo; Dorota Zarnowiecki; Claire Gardner; Shalem Leemaqz; Jennifer Arguelles; Astrid AM Poelman; Maeva O Cochet-Broch; David N Cox; Rebecca K Golley (Cambridge University Press, 2023)
Abstract Objective: To inform a package of initiatives to increase children's vegetable intake while in long day care (LDC) by evaluating the independent and combined effects of three initiatives targeting food provision, the mealtime environment and the curriculum. Design: Using the Multiphase Optimisation Strategy (MOST) framework, a 12-week, eight-condition (n 7 intervention, n 1 control) randomised factorial experiment was conducted. Children's dietary intake data were measured pre- and post-initiative implementation using the weighed plate waste method (1× meal and 2× between-meal snacks). Vegetable intake (g/d) was calculated from vegetable provision and waste. The optimal combination of initiatives was determined using a linear mixed-effects model comparing between-group vegetable intake at follow-up, while considering initiative fidelity and acceptability. Setting: LDC centres in metropolitan Adelaide, South Australia. Participants: 32 centres, 276 staff and 1039 children aged 2-5 years. Results: There were no statistically significant differences between any of the intervention groups and the control group for vegetable intake (all P > 0·05). The curriculum with mealtime environment group consumed 26·7 g more vegetables/child/day than control (ratio of geometric mean 3·29 (95 % CI 0·96, 11·27), P = 0·06). Completion rates for the curriculum (> 93 %) and mealtime environment (61 %) initiatives were high, and acceptability was good (4/5 would recommend), compared with the food provision initiative (0-50 % completed the menu assessment, 3/5 would recommend). Conclusion: A programme targeting the curriculum and mealtime environment in LDC may be useful to increase children's vegetable intake. Determining the effectiveness of this optimised package in a randomised controlled trial is required, as per the evaluation phase of the MOST framework.